The Effect of Mobile Banking Usage on Banking Customer Satisfaction - Ayu Maulidia; Silvia Anita Dewi; Moh.Yogi Nuruzzalam; Achmarul Fajar (Yayasan Kita Menulis, 2026)
The rapid development of information technology has encouraged the banking sector to innovate through digital-based services, one of which is mobile banking. This service provides convenience for customers in conducting banking transactions quickly, effectively, and efficiently through smartphones without having to visit bank offices. This study aims to determine the effect of mobile banking usage on customer satisfaction in banking services. The research method used is a quantitative descriptive approach with data obtained from previous journals and supporting literature related to mobile banking and customer satisfaction. The results indicate that the use of mobile banking has a positive and significant effect on customer satisfaction. Factors such as ease of use, transaction speed, security, service quality, trust, and digital banking innovation are proven to influence customer satisfaction in using mobile banking services. In addition, digital banking services are able to improve customer convenience and efficiency in carrying out financial transactions. Therefore, banks are expected to continuously improve the quality of digital services, strengthen transaction security systems, and provide sustainable innovations to maintain customer satisfaction and loyalty in the digital era.